2017
DOI: 10.1021/acs.jmedchem.7b01028
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Orally Bioavailable Macrocyclic Peptide–Peptoid Hybrid CXCR7 Modulators

Abstract: The chemokine receptor CXCR7 is an attractive target for a variety of diseases. While several small-molecule modulators of CXCR7 have been reported, peptidic macrocycles may provide advantages in terms of potency, selectivity, and reduced off-target activity. We produced a series of peptidic macrocycles that incorporate an N-linked peptoid functionality where the peptoid group enabled us to explore side-chain diversity well beyond that of natural amino acids. At the same time, theoretical calculations and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…Although no specific name was offered, Boehm et al recently reported a macrocyclic peptide-peptoid hybrid molecule, which binds to CXCR7 with high affinity ( K i < 100 nM) and measurable passive permeability ( P app > 5 × 10 -6 cm/s). The bioactive peptide 25 ( K i = 9 nM) achieved oral bioavailability of 18% in rats, which was commensurate with the observed plasma clearance values upon intravenous administration ( Boehm et al, 2017 ). In addition, FC313, a cyclic pentapeptide ligand for CXCR7, which is modified at the I-Pro position with a bulky hydrophobic side chain, exhibited an improved bioactivity toward CXCR7 ( Sekiguchi et al, 2018 ).…”
Section: Pharmacological Ligands Of Cxcr7supporting
confidence: 58%
“…Although no specific name was offered, Boehm et al recently reported a macrocyclic peptide-peptoid hybrid molecule, which binds to CXCR7 with high affinity ( K i < 100 nM) and measurable passive permeability ( P app > 5 × 10 -6 cm/s). The bioactive peptide 25 ( K i = 9 nM) achieved oral bioavailability of 18% in rats, which was commensurate with the observed plasma clearance values upon intravenous administration ( Boehm et al, 2017 ). In addition, FC313, a cyclic pentapeptide ligand for CXCR7, which is modified at the I-Pro position with a bulky hydrophobic side chain, exhibited an improved bioactivity toward CXCR7 ( Sekiguchi et al, 2018 ).…”
Section: Pharmacological Ligands Of Cxcr7supporting
confidence: 58%
“…FouchØ,e tal.,r ecently reported ah ighly membrane permeable cyclic decapeptide which showed that favorable ADME and PK properties can be achieved in synthetic cyclic peptides with molecular weights above 1000 Da (Figure 1a). [10] Since peptoids are derived from primary amines and can therefore extend the range of chemical functionality that can be incorporated into ac yclic peptide, [11] we initially set out to determine whether permeability could be maintained in this system upon substitution with peptoid residues. Serendipitously,w ef ound that peptoid substitutions in these macrocycles had as pecific effect on conformational flexibility,s uch that solvent-dependent chameleonicity could be tuned depending on the location of the peptoid substitutions within the scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Favorable permeability profiles were shown to be consistent and tolerant to variations in oligomer side chain type 65 . Recently, another hexameric peptoid-peptide macrocycle, designed as a CXCR7 modulator, was demonstrated to exhibit both membrane permeability and oral bioavailability in rats 66 . In addition to pharmacokinetic issues, there is the potential that targeting β-catenin will lead to on-target toxicity 67 .…”
Section: Discussionmentioning
confidence: 99%